2016
DOI: 10.1016/j.jviromet.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Consistent viral DNA quantification after prolonged storage at ambient temperature

Abstract: Long-term storage of biological specimens at low temperatures is costly and impractical in resource limited settings, where the disease burden of chronic viral infections is highest, and the need for research greatest. We examined the necessity of cold storage by comparing the quantity of HHV-8 DNA recovered from swab samples before and after 9–11 months of storage at temperatures of −20 °C, 4 °C and 37 °C. Quantitative levels of HHV-8 DNA remained consistent for laboratory or mucosal swab samples regardless o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Recently many studies have investigated the effects of various factors on virus survival but, less is known on the impact of temperature on SARS-CoV-2 RNA detection by RT- PCR ( Eslami and Jalili, 2020 ; Kim et al, 2021 ; Li et al, 2020 ; Xie and Zhu, 2020 ; Xu et al, 2020 ). In a limited number of studies related to other viruses (enterovirus, HSV-2, HHV-8, adenovirus, influenza), it has been reported that the storage of the samples at ambient temperature did not affect the test results ( Druce et al, 2012 ; Zaniello et al, 2016 ). Our results showed that oropharyngeal/nasopharyngeal samples kept at room temperature remain positive in SARS-CoV-2 real-time PCR studies for at least six days.…”
Section: Discussionmentioning
confidence: 99%
“…Recently many studies have investigated the effects of various factors on virus survival but, less is known on the impact of temperature on SARS-CoV-2 RNA detection by RT- PCR ( Eslami and Jalili, 2020 ; Kim et al, 2021 ; Li et al, 2020 ; Xie and Zhu, 2020 ; Xu et al, 2020 ). In a limited number of studies related to other viruses (enterovirus, HSV-2, HHV-8, adenovirus, influenza), it has been reported that the storage of the samples at ambient temperature did not affect the test results ( Druce et al, 2012 ; Zaniello et al, 2016 ). Our results showed that oropharyngeal/nasopharyngeal samples kept at room temperature remain positive in SARS-CoV-2 real-time PCR studies for at least six days.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a Dacron swab is inserted into the mouth and vigorously rubbed along the buccal mucosa, gums, and hard palate. The swab is then placed in 1 mL of filter-sterilized digestion buffer [ 59 ] and stored at ambient temperature [ 60 ] before being placed at -20°C for storage.…”
Section: Methodsmentioning
confidence: 99%
“…HHV-8 seropositivity was determined by positive test result on either immunofluorescence assay (IFA) against latent or lytic antibodies [ 39 ] or whole-virus enzyme immunoassay (EIA) [ 27 ]. Swabs were collected into lysis buffer containing 100 mM KCl (or NaCl), 25 mM EDTA (pH 8.0), 10 mM Tris (pH 8.0), and 1 % Igepal CA-630 and stored at −20 °C until testing, a process validated to be stable for extended storage [ 40 , 41 ]. Quantitative polymerase chain reaction (qPCR) was performed to quantitate HHV-8 DNA using previously described and validated methods [ 1 , 16 , 38 , 42 ].…”
Section: Methodsmentioning
confidence: 99%